Scalable database for observed climate hazards and impacts, climate finance and climate litigation cases in Africa - Engdaw, Mastawesha Misganaw; Ghosh, Aniruddha; Chilambe, Pedro Anglaze (2025)
Africa is widely recognized as a continent facing persistent data scarcity. Whether in observed climate, hydrological, or other environmental domains, the absence or poor quality of data remains a major challenge in accurately assessing the continent’s progress, understanding its current socioeconomic and environmental dynamics, and informing effective policies and future actions. The continent could achieve far greater outcomes if the quality, accessibility, and ownership of data—and the information derived from it—were improved. Beyond improving data quality, efforts in Africa should transform to data ownership. In the era of rapidly evolving, data-intensive artificial intelligence, Africa must transform from being data-lacking and externally dependent to becoming a continent of data ownership and ensure its digital sovereignty. Within this broader vision, this Innovation Brief documents an ongoing initiative to develop a scalable database for observed climate hazards and impacts, climate finance flows (and instruments), and climate litigation cases across Africa. Using state-of-the-art scientific methodologies and standards, the database will be enriched both retrospectively and proactively with rigorously verified information on observed climate hazards, their impacts, climate finance instruments, and the status and trends of climate-related litigation cases across the continent. Periodic analysis of the curated and managed data will provide critical insights to inform climate adaptation, mitigation and Loss and Damage policies. Moreover, the database will serve as a vital instrument to support Africa’s climate negotiations and strengthen efforts to mobilize climate finance. Beyond these immediate benefits, this transition toward data ownership will have significant and long-term implications for Africa’s digital sovereignty and evidence-based climate governance.